Functional Metalinguistic Comments in Parentheses in Martin Ford’s Book “Rise of the Robots” and Their Translation into Lithuanian - Gempler, Janina; Mikelionienė, Jurgita (Respectus Philologicus, 2024)
Research on the translation of metalinguistic comments (MLCs) in parentheses is rather scarce considering the relevance of the topic. The quality of the translation largely depends on the use of translation strategies such as the omission and addition of MLCs in the target texts as well as the retention or displacement of punctuation marks based on the function of the comment in the original language and the pragmatic aspects of punctuation. The aim of the study is twofold: to determine the functions of MLCs in parentheses in a popular science text and the strategies of their translation into Lithuanian. The study is mainly based on the typology of the functions of MLCs in parentheses and the classification of translation strategies, developed by Levin and Ström Herold (2021). The results of the study revealed that MLCs in parentheses in popular science texts were mostly used for the purposes of specification and were always retained in target texts. MLCs in parentheses that appeared only in the target text included cases of additions and shifts that were used to maximise the pragmatic effect, to highlight the author’s subjective opinion or to hide information that was not particularly relevant to the target reader. Omission, on the other hand, was more of a coincidence than a tendency.